If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 21Y + -8Y(2) = 6Y + 1 + -10 Reorder the terms for easier multiplication: 21Y + -8 * 2Y = 6Y + 1 + -10 Multiply -8 * 2 21Y + -16Y = 6Y + 1 + -10 Combine like terms: 21Y + -16Y = 5Y 5Y = 6Y + 1 + -10 Reorder the terms: 5Y = 1 + -10 + 6Y Combine like terms: 1 + -10 = -9 5Y = -9 + 6Y Solving 5Y = -9 + 6Y Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Add '-6Y' to each side of the equation. 5Y + -6Y = -9 + 6Y + -6Y Combine like terms: 5Y + -6Y = -1Y -1Y = -9 + 6Y + -6Y Combine like terms: 6Y + -6Y = 0 -1Y = -9 + 0 -1Y = -9 Divide each side by '-1'. Y = 9 Simplifying Y = 9
| 23-7+4(x-1)=11 | | 8y-3y+6=-10 | | x*.10=14.79 | | 27r^3+1=0 | | 19-2x-3=2x+6+x | | 7x-15=2x+10 | | 3x^2+7x+2=y | | 5x+12+6x=93+2x | | h=-10t^2+90 | | 3x-1=2x+2+1 | | 3x^3+25x^2+28x=0 | | 4(n+2)=9n-7 | | 2y-1+y=-2+13-2y | | x+y=-400 | | 4x+2x-60=48 | | 2p-10-2=12-p-p | | r^3+3r^2=0 | | v+1-2v=4 | | 3n+15=7n-1 | | 4+3n+2=-9 | | y=2cos(3x+1) | | -4=2x+x | | 4n+8=5n-2 | | 4*log(x-9)=3 | | -1+7x=-186 | | 7e^9t=11e^8t | | 15=-6n+3n | | -7r=-21 | | p+6=2 | | x^4-49x^2-360=0 | | y-8=4x | | a^3+b^2=72 |